Environmental biotechnology - Srinivas, T. (New Age International (P) Ltd., Publishers, 2008)
About the Book: This book is meant for undergraduate students of Biotechnology, Chemical and Civil Engineering courses and also for postgraduate students of Environmental Studies. It encompasses topics related to pollution abatement and treatment of wastewater and solid waste management emphasizing on biological treatment methods. Design aspects of the biological treatment units are the distinctive features of this book. Principles of bioremediation are briefly covered. Contents: Water and Wastewater Treatment of Wastewater Wastewater Biology Secondary Treatment (Biological Treat.